KEMANDIRIAN SISWA DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM - Arif Ridha (El-Rusyd, 2020)
Independent learning is one of the factors that determine the success of students in learning, so that these self-important attitude is owned by anyone who wants to achieve success in life. Parents have a very important role in shaping the autonomy of their children, including in independent learning. This is because the parents who become the first and primary educators. In other words, parents may be responsible first and foremost to the education of their children. This study aims to determine an effort to increase student independence in learning as well as factors inhibiting PAI and supporting efforts to increase the independence of students in SDN 21 PAI in the District IV Koto Koto Tuo Agam. This research is a field research by using descriptive method. The population in this study is the first person PAI teachers and 120 students of class I s / d class VI, by sampling using purposive random sampling, which is 32 students. To get the data the authors used observations, questionnaires and interviews. Questionnaires given to the students, while the authors do an interview to the principal and teachers PAI.